1999
DOI: 10.1046/j.1460-9568.1999.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Raf‐1 and B‐Raf proteins have similar regional distributions but differential subcellular localization in adult rat brain

Abstract: The Raf kinases play an important and specific role in the activation of extracellular signal-regulated kinases (ERK) cascade. Beside its role in the control of proliferation and differentiation, the ERK cascade has also been implicated in neuron-specific functions. In order to gain clues on the function of Raf kinases in the adult central nervous system (CNS), we performed a comparative analysis of the distribution and subcellular localization of the different Raf kinases in rat brain with antibodies specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
38
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 59 publications
10
38
0
2
Order By: Relevance
“…Consistent with its mRNA and protein levels, the activity of Raf-1 in both PFC and hippocampus was weaker than that of B-Raf. Our protein expression studies are somewhat similar to those reported by Morice et al, 44 who found that immunolabeling of B-Raf (B98 kDa band) was higher in hippocampus than cortex. However, contrary to our results, they found similar levels of Raf-1 expression in both PFC and hippocampus.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with its mRNA and protein levels, the activity of Raf-1 in both PFC and hippocampus was weaker than that of B-Raf. Our protein expression studies are somewhat similar to those reported by Morice et al, 44 who found that immunolabeling of B-Raf (B98 kDa band) was higher in hippocampus than cortex. However, contrary to our results, they found similar levels of Raf-1 expression in both PFC and hippocampus.…”
Section: Discussionsupporting
confidence: 91%
“…33,43 Raf-1 gene expression has been detected in all cell lines and tissues examined, with highest levels in brain although mRNA signal for Raf-1 in the brain is much weaker than that of B-Raf. 33 More recently, Morice et al 44 have shown that at the cellular level, both Raf-1 and B-Raf immunostaining is mostly localized in neurons. They also found that both these proteins are localized not only within the same brain areas but also within the same cells in rat brain; however, the intensities of the immunostaining were different, depending upon the brain structure.…”
Section: Discussionmentioning
confidence: 99%
“…B-Raf expression shows the most diverse expression patterns of the Raf family members in the nervous system. It can be cellspecific within a neuronal tissue (Dugan et al 1999) and subcellular-specific within an individual cell (Derkinderen et al 1999;Morice et al 1999). In agreement with these reports, B-Raf displays a distinct cell-specific and subcellular expression pattern in the avian auditory epithelium.…”
Section: B-raf Is a Key Excitatory Link Between The Camp/ Pka And Erkmentioning
confidence: 65%
“…The structures appear to cluster around the borders of the hair cells. B-Raf is a cytoplasmic signaling protein and the expression of B-Raf can be restricted to distinct subcellular regions such as neuronal dendrites and cell bodies (Derkinderen et al 1999;Morice et al 1999). The punctate B-Raf structures may represent cytoplasmic B-Raf signaling complexes that clustered to discrete lumenal regions of supporting cells.…”
Section: B-raf Expression Is Localized To Supporting Cells In the Avimentioning
confidence: 99%
“…B-RAF KIN/KIN mice were created that express A-RAF under control of endogenous B-RAF promoter, and we expected that neurons would survive beyond the critical midgestation cell death phase. Because we had previously observed that B-RAF overexpression can mediate neurite outgrowth (47) and because B-RAF localizes to axons and dendrites in vivo (25), we wanted to study these aspects of B-RAF function in neuronal differentiation.…”
mentioning
confidence: 99%